The influence of feed and depth on the operation of bubu fishing tools in Pangkalan Kuras District, Pelalawan Regency, Riau Province - Zega, Melvi Purnama Fajar; Bustari, Bustari; Nasution, Polaris (Science, Technology, and Education Care, 2024)
The purpose of this study was to determine the weight of the bait and the effective depth for operating traps in Kesuma Village, Pangkalan Kuras District, and Pelalawan Regency. The bait weight is divided into 50 g, 100 g, and 150 g, while the depth is divided into 1 m and 5 m. This research was carried out in January 2022 at the Nilo River in Kesuma Village. The method used in this study was the experimental fishing method with a randomized group design factor. The test results of the analysis of variance on the number of catches show that there is an influence of bait, depth, and interaction between the two, or a value of Fcount > Ftable. The test results of the analysis of variance on catch weight showed that there was an effect of bait and depth because the value of Fcount > Ftable, while the interaction of bait and depth had a value of Fcount < Ftable, so there was no interaction effect on catch weight. Based on the results of the Least Significant Difference (LSD) further test, it is known that the effective weight of oil palm bait to get a larger number of catches is 150 g at a depth of 5 m, while to get heavier catches, the trap will be effective at a depth of 1 m with a bait weight of 150 g.